New Perspectives in Critical Data Studies The Ambivalences of Data Power - Hepp, Andreas; Jarke, Juliane; Kramp, Leif.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This Open Access book examines the ambivalences of data power. Firstly, the ambivalences between global infrastructures and local invisibilities challenge the grand narrative of the ephemeral nature of a global data infrastructure. They make visible local working and living conditions, and the resources and arrangements required to operate and run them. Secondly, the book examines ambivalences between the state and data justice. It considers data justice in relation to state surveillance and data capitalism, and reflects on the ambivalences between an entrepreneurial state and a welfare state. Thirdly, the authors discuss ambivalences of everyday practices and collective action, in which civil society groups, communities, and movements try to position the interests of people against the big players in the tech industry. The book includes eighteen chapters that provide new and varied perspectives on the role of data and data infrastructures in our increasingly datafied societies. Andreas Hepp is Professor of Media and Communications and Head of ZeMKI, Centre for Media, Communication and Information Research, University of Bremen, Germany. He is the author of 12 monographs including The Mediated Construction of Reality (with Nick Couldry, 2017), Transcultural Communication (2015) and Cultures of Mediatization (2013). Juliane Jarke is a senior researcher at the Institute for Information Management Bremen (ifi b) and Centre for Media, Communication and Information Research (ZeMKI) at the University of Bremen, Germany. Jarke co-edited The Datafication of Education (with Andreas Breiter, 2019) and Probes as Participatory Design Practice (with Susanne Maaß, 2018). Leif Kramp is a post-doctoral media, communication and history scholar and Research Coordinator of the Centre for Media, Communication and Information Research at the University of Bremen (ZeMKI), Germany. Kramp has authored and edited various books about the transformation of media and journalism and is a founding member of the German Association of Media and Journalism Criticism (VfMJ).
New Perspectives in Critical Data Studies: The Ambivalences of Data Power An Introduction -- Part I Global Infrastructures and Local Invisibilities -- Data Power and Counter-power with Chinese Characteristics -- Transnational Networks of Influence: The Twitter Presence of the Quantified Self and Maker Movements Organizational Elites -- The Power of Data Science Ontogeny: Thick Data Studies on the Indian IT Skill Tutoring Microcosm -- Fighting the System: A Pilot Project on the Opacity of Algorithms in Political Communication -- Indigenous Peoples, Data, and the Coloniality of Surveillance -- Part II State and Data Justice -- The Datafied Welfare State: A Perspective from the UK -- The Value Dynamics of Data Capitalism: Cultural Production and Consumption in a Datafied World -- Mapping Data Justice as a Multidimensional Concept Through Feminist and Legal Perspectives -- Reconfiguring Education Through Data: How Data Practices Reconfigure Teacher Professionalism and Curriculum -- Public Values and Technological Change: Mapping how Municipalities Grapple with Data Ethics -- Welfare Data Society? Critical Evaluation of the Possibilities of Developing Data Infrastructure Literacy from User Data Workshops to Public Service Media -- Part III Everyday Practices and Collective Action -- (Not) Safe to Use: Insecurities in Everyday Data Practices with Period-Tracking Apps -- Community Rankings and Affective Discipline: The Case of Fandometrics -- Affinity Spaces as an Analytical Lens for Attending to Temporality in Critical Data Studies: The Case of COVID-19-Related, Educational Twitter Communication -- Party like it s December 31, 1983: Supporting Data Literacy at CryptoParties -- Researching Public Trust in Datafication: Reflections on the Deliberative Citizen Jury as Method -- Worker Perspectives on Designs for a Crowdwork Co-operative -- Counting, Debunking, Making, Witnessing, Shielding: What Critical Data Studies Can Learn from Data Activism During the Pandemic.
Keywords: Digital media; Technology -- Sociological aspects; Information technology; Digital and New Media; Information and Communication Technologies (ICT).